Systematic Literature Review: Determination of Government Policy in Health and Education Development for Improved Human Capital - Rizki Afri Mulia; Nika Saputra (Jurnal EL-RIYASAH, 2021)
Human capital plays a very strategic role in supporting the competitiveness of a country or region. This study aims to determine how the development of human capital is seen from the theoretical and practical settings and how the solutions are resolved. With the approach pattern, Systematic Literature Review in the journal already is published since the year 2011 until 2021 it got the result that human capital research is currently focused on two topics and trends: the development of education and health. The method often used in human capital research is a quantitative approach of 62%, a qualitative approach of 36% and a mixed-method approach of 2%. The cause of the low increase in human capital is the lack of government attention in improving education and health. The solution given to answer the problem of low human capital is by improving the quality of education and improving public health facilities to achieve better human capital. To achieve this goal, the government plays an important role in this increase.